Successful control of juvenile dermatomyositis-associated macrophage activation syndrome and interstitial pneumonia: distinct kinetics of interleukin-6 and -18 levels. Issue 1 (December 2015) - Wakiguchi, Hiroyuki; Hasegawa, Shunji; Hirano, Reiji; Kaneyasu, Hidenobu; Wakabayashi-Takahara, Midori; Ohga, Shouichi
Abstract Background Macrophage activation syndrome (MAS) is the secondary hemophagocytic lymphohistiocytosis associated with rheumatic diseases. Recently, the different cytokine profiles between systemic juvenile idiopathic arthritis (sJIA)-associated MAS (sJIA-MAS) and juvenile systemic lupus erythematosus (JSLE)-associated MAS (JSLE-MAS) were reported. However, there is little information about juvenile dermatomyositis (JDM)-associated MAS (JDM-MAS). Case presentation A 4-year-old girl with JDM was hospitalized because of fever, erythema, hepatosplenomegaly, cytopenia, liver dysfunction and coagulopathy. Bone marrow aspiration revealed appreciable numbers of activated and hemophagocytosing macrophages. She was diagnosed as having JDM–MAS complicated with interstitial pneumonia (IP) based on the findings of the elevation of serum Krebs von den Lungen-6 (KL-6) levels and chest computed tomography findings. We analyzed circulating levels of interleukin (IL)-2, 4, 6, 10, 18, tumor necrosis factor-α and interferon-γ in the patient. Hypercytokinemia occurred at the diagnosis of MAS and IP, showing with the prominent elevations of IL-6 and IL-18 levels. The cytokine profiles were distinct from those reported in patients with sJIA-MAS or JSLE-MAS. High-dose corticosteroid and cyclosporine therapy led to a drastic improvement of MAS with decreased IL-6 levels. Subsequent cyclophosphamide therapy successfully controlled IP, paralleled with the declining pattern of IL-18 and KL-6 levels. Conclusion This is the first report to describe a successful treatment and the cytokine profile of JDM-MAS and IP. Serum IL-6 and IL-18 levels may be useful for predicting the disease activity of JDM-MAS and IP, respectively.